2016
DOI: 10.18203/2320-6012.ijrms20164222
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis in adults: not so rare

Abstract: Shahab-ud-din Bukhari 1 INTRODUCTION Tinea capitis is the dermatophyte infection of the scalp with varied clinical presentation. Tinea capitis is predominantly seen in preadolescent adults and is rare in adults. In adults cases generally occur in immunocompromised patients. Tinea capitis may be rare in adults due to the fungistatic activity of long chain saturated fatty acids in sebum which appear after puberty and unknown immunological factors. 1 Colonization by Malassezia globosa may interfere with dermatoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast, Romano et al 14 suggested that increased contact with animals, immune system defects in patients and the strong capacity of M. canis to adapt to environmental changes might contribute to the predominance of M. canis in Italy. T. violaceum , another common causative agent of adult tinea capitis, is the most prevalent aetiology in countries in Asia (China, 23–25 India 45 ), Africa (South Africa, 46 Senegal 47 ) and the Middle East (Egypt, 19 Tunisia, 20 Morocco, 21 Pakistan, 22 Iran 1 ). Some European counties including Spain 4 and Greece 8 are also endemic areas of T. violaceum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Romano et al 14 suggested that increased contact with animals, immune system defects in patients and the strong capacity of M. canis to adapt to environmental changes might contribute to the predominance of M. canis in Italy. T. violaceum , another common causative agent of adult tinea capitis, is the most prevalent aetiology in countries in Asia (China, 23–25 India 45 ), Africa (South Africa, 46 Senegal 47 ) and the Middle East (Egypt, 19 Tunisia, 20 Morocco, 21 Pakistan, 22 Iran 1 ). Some European counties including Spain 4 and Greece 8 are also endemic areas of T. violaceum .…”
Section: Discussionmentioning
confidence: 99%
“…T. violaceum, another common causative agent of adult tinea capitis, is the most prevalent aetiology in countries in Asia (China, [23][24][25] India 45 ), Africa (South Africa, 46 Senegal 47 ) and the Middle East (Egypt, 19 Tunisia, 20 Morocco, 21 Pakistan, 22 Iran 1 ). Some European counties including Spain 4 and Greece 8 are also endemic areas of T. violaceum.…”
Section: Microsporum Species But Not Against Endothrix Infections Cau...mentioning
confidence: 99%